CCAUSES OF MISMANAGEMENT OF SCHOOL FINANCES IN MREWA DISTRICT SECONDARY SCHOOLS - MUZENDA, DR DENIAS (IJRDO- Journal of Educational Research, 2017)
This study sought to find out the challenges faced by school heads in the management of schoolfinances in Mrewa District. The population comprised all the secondary schools in the district.Random sampling was used to come up with a sample of ten (10) schools from where 40respondents were purposively selected. The study adopted the descriptive survey design and thequestionnaire and interview were used as the research instruments for collecting data. The studyestablished that most heads lacked the accounting literacy required for effective management ofschool finances, and that there was little or no supervision at all from the Ministry of Primaryand Secondary Education finance department personnel on financial management issues. Thestudy recommends that there should be capacity building programmes for heads of schools,deputy heads as well as members of the school development committees. The Ministry ofPrimary and Secondary Education should increase both announced and unannounced visits toschools to monitor the use of finances in the schools.